Digital Technology Shaping Teaching Practices in Higher Education - Akbar, Monika (Frontiers in ICT, 2016)
In their quest on being effective, educators have always experimented with the art of teaching. Teaching has evolved over centuries by adopting new approaches, methods, tools, and technologies to reach a wider audience. As technologies advance, educators should carefully use, evaluate, and adopt the changes to utilize the technologies and track of their impacts. This article provides a mini review to briefly describe some of the existing technical achievements that are used in higher education along with their challenges.